Mining Textiles: Extracting multi-narrative responses from textiles to rethink a mining past - Barber, Claire (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
This article is evidence of a practice-based investigation into the imaginative worlds of mining and textiles as a starting point for transforming ways of thinking and creating in the locality. Featuring artist-in-residence and archival processes of research, and performative and site-responsive interventions, a number of recurring themes of enquiry will be developed that combine elements of clothing design, historical studies, nature studies, photography, inflatable construction and social anthropology. The article will draw from the authors artistic practice in the extraction of multi-narrative responses from textiles as an inventive method for engaging site-specifically with former mining locations in UK and Australia.